2011
DOI: 10.1103/physreve.83.026312
|View full text |Cite
|
Sign up to set email alerts
|

Analytical derivation of tortuosity and permeability of monosized spheres: A volume averaging approach

Abstract: Macroscopic properties of granular materials are important in modeling a variety of flow and transport phenomena in many fields of science. Determination of these parameters has always been an issue among both researchers and engineers, mainly in view of tortuosity and permeability. This paper presents analytical functions for the tortuosity and permeability of monosized sphere arrays based on a volume averaging approach and eliminates some ambiguities by modification of the original representative elementary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(81 citation statements)
references
References 36 publications
7
72
2
Order By: Relevance
“…The discussion until now has confirmed that material particle size, material sorting and material geometry all significantly influence the hydraulic conductivity [50,[52][53][54]. In Fe 0 beds, in-situ generated iron hydroxides tend to cement initial particles and decrease both porosity and permeability.…”
Section: Permeability Lossmentioning
confidence: 88%
See 1 more Smart Citation
“…The discussion until now has confirmed that material particle size, material sorting and material geometry all significantly influence the hydraulic conductivity [50,[52][53][54]. In Fe 0 beds, in-situ generated iron hydroxides tend to cement initial particles and decrease both porosity and permeability.…”
Section: Permeability Lossmentioning
confidence: 88%
“…4) was essentially lower for ZVI1 than for ZVI10 and ZVI9. This behaviour is primarily attributed to the material sorting [50][51][52][53][54]. In fact, a packed bed of a better sorted granular material exhibits a greater permeability.…”
Section: Mb Discolorationmentioning
confidence: 99%
“…Its relations to porosity have been reported in various forms of relation [5,6]. In this work instead of tortuosity another related term, average tortuosity, is introduced, which is averaged though all possible values within certain value of porosity.…”
Section: Introductionmentioning
confidence: 99%
“…1a). The geometric tortuosity may be obtained with the use of experimental (CT/IA techniques [3,7,24], acoustic [4][5][6], electrical [22] and others [25]), analytical [11,16,17] or computational methods Fig. 1 The visualization of the tortuosity definition: a geometric, b hydraulic (a) (b) [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…In many investigations a direct correlation between tortuosity and porosity is assumed (e.g. [16][17][18][19]). It was stated that the tortuosity decreases if the porosity increases [20][21][22].…”
Section: Introductionmentioning
confidence: 99%